Volatilité de l’espace politique en Afrique : le Bénin à la quête d’une identité politique - HOUENOU, Seminakpon Arnaud (Studia Universitatis Babes-Bolyai Studia Europaea, 2025)
Volatility of Political Space in Africa: Benin’s Quest for a Political Identity. The Republic of Benin is undergoing a fundamental normative reform of its political space. In just over eight years of power at the head of the Republic of Benin, the regime of President Talon introduced governance marked by a double rupture. The first consists of strict control of the Beninese political space through the establishment of a new legislation and the second a restoration of State authority through a vertical exercise of State power including the purpose is the control of the political institutions of the Republic. Theorized as the governance of the “Rupture”, the regime of President Patrice Talon due to its tendency to operate outside the framework defined by the political contract obtained following a laborious consensus during the Conference of Forces of the Nation in 1990. This democratic shift in the “Rupture” regime inaugurates a new political identity in its functioning which time will allow to see how well it has taken root.